An Interaction between Praseodymium 4-Hydroxycinnamate with AS1020 and X65 Steel Microstructures in Carbon Dioxide Environment. Issue 2 (18th January 2018) - Nam, N. D.; Panaitescu, C.; Tan, M. Y. J.; Forsyth, M.; Hinton, B.
Abstract : This work reports on the application of a rare earth organic compound, praseodymium 4-hydroxycinnamate - Pr(4OHCin)3, as an effective inhibitor suitable for preventing carbon dioxide corrosion of steels in an aggressive environment. Two steels, namely an AS1020 and a X65 steel, have been tested in 0.01 M NaCl solution saturated with carbon dioxide gas using electrochemical and surface analysis techniques. The results show that X65 steel is less susceptible to corrosion than AS1020 steel in CO2 -saturated 0.01 M NaCl solution as indicated by a lower corrosion current density and a higher polarization resistance. On the other hand, the AS1020 was inhibited much more effectively by praseodymium 4-hydroxycinnamate compound in comparison with X65 steel, as the corrosion behavior of AS1020 and X65 steels was similar in the presence of the inhibitor. However, the inhibiting effects on the anodic reaction was greater for AS1020 due to a reduction in the anodic current density in comparison with X65 steel. The dramatic effect of praseodymium 4-hydroxycinnamate compound could be attributed to the protective inhibiting deposits and enhanced film formation on the more active steel surface.